Efficacy and Safety of an Herbal Therapy in Patients with Amnestic Mild Cognitive Impairment: A 24-Week Randomized Phase III Trial. (17th May 2017) - Tian, Jinzhou; Shi, Jing; Li, Tao; Li, Lin; Wang, Zhiliang; Li, Xiaobin; Lv, Zhu; Zheng, Qingshan; Wei, Mingqing; Wang, Yongyan
Abstract : Objective . In the 24-week randomized, double-blind, double-placebo, parallel-controlled trial, we aimed to test the effects of herbal therapy with amnestic mild cognitive impairment (aMCI). Methods . A total of 324 patients with aMCI entered a 2-week placebo run-in period followed by 24 weeks' treatment of either (a) herbal capsule (5 shenwu capsules/administration, 3 times/day) and placebo identical to donepezil tablets (n = 216 ) or (b) donepezil (5 mg/day) and placebo identical to herbal capsule (n = 108 ). Results . Herbal therapy showed a significant improvement on the primary efficacy measure, measured by Alzheimer Disease Assessment Scale-cognitive subscale (ADAS-cog), and showed a mean decrease from baseline of 4.23 points at the endpoint, without a significant difference from the donepezil group. Secondary efficacy measurement of the Logical Memory II Delayed Story Recall subtest (DSR) showed modest improvement in those taking herbal capsule compared to baseline, and there was no significant difference from donepezil group. The frequency of adverse events was much less in the herbal therapy group than the donepezil. Conclusion . Herbal therapy demonstrated a significant improvement in cognition and memory, which were similar to the donepezil in patients with aMCI. Herbal therapy was safe and well tolerated. Trial Registration . This study is registered with clinicaltrials.gov NCT01451749 .